Verb Phrase Structure in the Bajo Language - Siti Nuralisa Bahudin; Mohammad Tahir; Arum Pujining Tyas; Syamsuddin Syamsuddin; Idris Patekkai (Civiliza Publishing, Indonesia., 2026)
Language is the main communication tool used by humans to convey thoughts, feelings and wills. Each language has its own systems and rules, both in the fields of phonology, morphology, syntax, and semantics. This study aims to describe the structure of verb phrases in the Bajo language used by the people of Lomba Village, Lamala District, Banggai Regency. The focus of the research includes the structure of intransitive and transitive verb phrases and their formation patterns. The method used is a qualitative descriptive method with data collection techniques in the form of the see-through method and the cakap method. Data were obtained from the oral speech of native Bajo speakers as well as relevant written data. Data analysis was carried out using matching methods and distributional methods. The results of the study show that verb phrases in the Bajo language consist of intransitive verb phrases and transitive verb phrases. The structure of the verb phrase is formed by the relationship between the core element (the verb as upstream) and the additional element (adverbial, complementary, or operator). Three main patterns were found in intransitive verb phrases, namely the H–T (Upstream–Additional), T–H (Additional–Upstream), and T–H–T (Additional–Upstream–Additional). In transitive verb phrases, a similar pattern is also found, but with the presence of an object as a mandatory complement. In addition, in the structure of the Bajo verb phrase there is the use of grammatical operators such as negation markers, aspects, and prohibitions that affect the overall meaning of the phrase. This research is expected to contribute to the development of linguistic studies, especially in the field of regional language syntax, as well as support efforts to preserve the Bajo language as part of Indonesia's cultural wealth